2010
DOI: 10.1590/s1516-89132010000100025
|View full text |Cite
|
Sign up to set email alerts
|

Physiochemical parameters optimization for enhanced nisin production by Lactococcus lactis (MTCC 440)

Abstract: The influence of various physiochemical parameters on the growth of Lactococcus lactis sub sp. lactis MTCC 440 was studied at shake flask level for 20 h. Media optimization (MRS broth) was studied to achieve enhanced growth of the organism and also nisin production. Bioassay of nisin was done with agar diffusion method using Streptococcus agalactae NCIM 2401 as indicator strain. MRS broth (6%, w/v) with 0.15µg/ml of nisin supplemented with 0.5% (v/v) skimmed milk was found to be the best for nisin production a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…2). The decrease in the pH with decreased buffering capacity of the medium also was observed by Mall et al (2010). For the same storage period (Fig.…”
Section: Evaluation Of the Stability Ph And Aciditysupporting
confidence: 63%
“…2). The decrease in the pH with decreased buffering capacity of the medium also was observed by Mall et al (2010). For the same storage period (Fig.…”
Section: Evaluation Of the Stability Ph And Aciditysupporting
confidence: 63%
“…Nisin production by lactic acid bacteria is known to be temperature dependent. Mall et al investigated the influence of various parameters on L. lactis growth in broth to enhance nisin production . They found that nisin production was affected by temperature, with maximum nisin production at 30°C.…”
Section: Resultsmentioning
confidence: 99%
“…Optimum cell growth temperature promotes cell growth and thus the optimum yield of nisin. Under normal conditions, the optimal production temperature of nisin is 30 °C, while the biomass yield is increased at 37 °C (Mall et al., 2010). The optimum temperature for growth and bacteriocin production of various LAB strains was significantly correlated with strains (Abbasiliasi et al ., 2017).…”
Section: Optimization Of Nisin Productionmentioning
confidence: 99%